Bioactive Compounds and Antioxidant, Antiperoxidative, and Antihemolytic Properties Investigation of Three Apiaceae Species Grown in the Southeast of Morocco. (23rd September 2020) - Derouich, Mgal; Bouhlali, Eimad Dine Tariq; Bammou, Mohamed; Hmidani, Abdelbasset; Sellam, Khalid; Alem, Chakib
Abstract : For a long time, Apiaceae species have been widely employed in the southeast of Morocco for culinary and folk healing purposes. In the current study, we investigated three Apiaceae herbs known as coriander ( Coriandrum sativum ), celery ( Apium graveolens ), and parsley ( Petroselinum crispum ) for their antioxidant, antiperoxidative, and antihemolytic properties. The HPLC-DAD has been used to classify and measure phenolic compounds. The major phenolic compounds studied were p-coumaric, chlorogenic, caffeic acids, luteolin, and quercetin. The polyphenol level was also estimated via Folin–Ciocalteu's method, aluminium chloride, and acidified vanillin. Parsley showed the highest polyphenol level and, thus, showed potential antioxidant activities demonstrated by DPPH, ABTS scavenging tests, and reducing power (FRAP), as well as TBARS assays. Very strong correlations were depicted among phenol levels and antioxidant assays ( R 2 ≥ 0.910) and among antihemolytic activity and flavonoids ( R 2 ≥ 0.927), indicating the implication of phenolic compounds, mainly flavonoids, in the antiradical properties. These finding may prove the traditional use of these Apiaceae species in the management of numerous disorders cited within the Moroccan pharmacopoeia.